CBD-enriched medical cannabis for intractable pediatric epilepsy: The current Israeli experience. (February 2016) - Tzadok, Michal; Uliel-Siboni, Shimrit; Linder, Ilan; Kramer, Uri; Epstein, Orna; Menascu, Shay; Nissenkorn, Andrea; Yosef, Omer Bar; Hyman, Eli; Granot, Dorit; Dor, Michael; Lerman-Sagie, Tali; et al.
Highlights: CBD-enriched medical cannabis is a promising treatment for intractable epilepsy. Only minor and infrequent side effects were reported. Epileptic encephalopathies respond better to CBD-enriched medical cannabis. Abstract: Purpose: To describe the experience of five Israeli pediatric epilepsy clinics treating children and adolescents diagnosed as having intractable epilepsy with a regimen of medical cannabis oil. Methods: A retrospective study describing the effect of cannabidiol (CBD)-enriched medical cannabis on children with epilepsy. The cohort included 74 patients (age range 1–18 years) with intractable epilepsy resistant to >7 antiepileptic drugs. Forty-nine (66%) also failed a ketogenic diet, vagal nerve stimulator implantation, or both. They all started medical cannabis oil treatment between 2–11/2014 and were treated for at least 3 months (average 6 months). The selected formula contained CBD and tetrahydrocannabinol at a ratio of 20:1 dissolved in olive oil. The CBD dose ranged from 1 to 20 mg/kg/d. Seizure frequency was assessed by parental report during clinical visits. Results: CBD treatment yielded a significant positive effect on seizure load. Most of the children (66/74, 89%) reported reduction in seizure frequency: 13 (18%) reported 75–100% reduction, 25 (34%) reported 50–75% reduction, 9 (12%) reported 25–50% reduction, and 19 (26%) reported <25% reduction. Five (7%) patients reported aggravation of seizures which led to CBD withdrawal. In addition, we observed improvement in behavior and alertness, language, communication, motor skills and sleep. Adverse reactions included somnolence, fatigue, gastrointestinal disturbances and irritability leading to withdrawal of cannabis use in 5 patients. Conclusions: The results of this multicenter study on CBD treatment for intractable epilepsy in a population of children and adolescents are highly promising. Further prospective, well-designed clinical trials using enriched CBD medical cannabis are warranted.